Подготовка студенток педагогического университета к спортивно-массовой работе по аэробике в школе - Леонова, В.; Куц, А.; Швец, О.; Leonova, V.; Kuts, A.; Shvets, O. (Східноєвропейський національний університет ім. Лесі Українки, 2012)
В статье поданна характеристика работы, подготовка студенток к разным формам спортивной работы в школе средствами аэробики, основные пути повышения уровня подготовки студенток к работе в школе из аэробики и результаты экспериментальных исследований. . The description of work is given in the article, preparation of students to different forms of sports work at schools by facilities of aerobics, basic ways of increasing of level of preparation among students to work at school from aerobics and results of experimental researches.
Preparation of Students of Pedagogical University to Sports and Community Work in Aerobics at Schools.
Keywords: студентки; спортивно-массовая работа; школа; аэробика; формы; средства; исследования; students; sports and community work; school; aerobics; forms; facilities; researches